A promising high-efficiency photovoltaic alternative non-silicon material: A first-principle investigation. (November 2018) - Rasukkannu, Murugesan; Velauthapillai, Dhayalan; Ponniah, Vajeeston
Abstract: We demonstrate by means of first-principle calculations that the band structure of TlBiS2 characterizes this material as a promising candidate for photovoltaic applications. Two calculation hybrid functional models are used, one including the spin-orbit coupling and one neglecting it. These calculations show that TlBiS2 has a direct band gap of 1.10 eV in the absence of spin-orbit coupling and 0.67 eV for spin-orbit coupling. The absorption peaks appear in the visible region with a consequently high absorption intensity for both without and with spin-orbit coupling. We show how computational modeling of TlBiS2 can substantially enrich the understanding of photovoltaic properties. Graphical abstract: Unlabelled Image